A study on prevalence of insomnia among middle aged women attending a tertiary care hospital, West Bengal - Kumari, Amrita; Banarjee, Ankita; Saha, Avishek (International Journal Of Community Medicine And Public Health, 2024)
Background: Insomnia is one of the common but neglected conditions seen in family practice. During the menopausal transition, significant sleep disruptions are provoked by sleep disorders. Insomnia is estimated to affect up to 30% of the general population and women are almost twice as likely as men to develop it. Objective was to find the prevalence of insomnia among middle-aged women. Methods: This descriptive, cross-sectional study was done for 3 months at general OPDS and IPDs of a tertiary care hospital among 40-60-year-old women fulfilling inclusion criteria. The sampling technique was convenience sampling. Data were analyzed using Microsoft Office Excel and analyze by SPSS version 25. Results: Of 310 participants, 45% had insomnia based on AIS-8. The maximum number of study participants fall under the age group of 40-45 years (33.23%) and under the socio-economic group lower-middle class (25.81%) according to the modified B. G. Prasad scale. Conclusions: The study concludes a significant occurrence of insomnia in middle-aged women in addition to menopausal symptoms. Implementation of appropriate health educational programs for preventing insomnia in such women is necessary.